[PP.23.06] PREDICTORS OF BLOOD PRESSURE RESPONSE IN THE NON-INVASIVE RENAL DENERVATION STUDY USING EXTERNALLY DELIVERED FOCUSED ULTRASOUND IN SEVERE RESISTANT HYPERTENSION. (September 2016) - OTT, C.; Dawood, O.; Starek, Z.; Kay, P.; Anderson, T.; Gertner, M.; Ormiston, J.; Neuzil, P.; Schmieder, R.E.
Abstract : Objective: The Kona Medical Surround Sound™ System is a non-invasive device for renal denervation that delivers externally focused ultrasound to the renal nerves using Doppler-based image guidance. The objective is to evaluate the predictors of blood pressure (BP) response. Design and method: In 3 consecutive studies patients with severe treatment resistant hypertension (TRH), defined as persistent systolic blood pressure (BP) > 160 mmHg despite 3 or more antihypertensive medications, were treated non-invasively with the Kona Medical Surround Sound System™. Focused ultrasound energy was delivered to the renal arteries bilaterally and surrounding tissue using Doppler-based imaging and continuous tracking with automatic correction for kidney motion throughout treatment. Results: In 65 patients with TRH the mean changes from baseline BP were −24.4/-10.2 mmHg at 12 weeks and −23.5/-8.8 mmHg at 24 weeks after renal denervation. No serious intervention related events have been reported to date. No significant heterogeneity occurred (see figure) across the various subgroups. Numerically, patients with systolic BP > 180 mmHg had 2 fold greater BP decreases, whereas patients with diabetes (N = 15) responded less favorably, potentially related to more advanced aortic stiffness. Conclusions: Our results showed clinically meaningful reductions in office BP after 6 months across all subgroups and no significantly heterogeneous BP decreases were observed.